THE ROLE OF EARLY CLAMPING OF UTERINE ARTERY AND DELAYED PLACENTAL SEPARATION IN REDUCING CONSEQUENCES OF PLACENTA ACCRETA SPECTRUM (PAS) DISORDER - Hussein, Tahir Abdullah; Abdullah, Naz Azad; Mahmood, Maryam Bakr; Hawrami, Jwan Maasoum; Barzinj, Nigar Mohammed Salih (Journal of Sulaimani Medical College, 2022)
Background Abnormal invasive placentation leads to massive intraoperative bleeding and maternal morbidity or death. The current study aimed to evaluate the role of systemic pelvic devascularization technique in reducing cesarean hysterectomy in pregnancies involved in PAS and its complication. Objectives To deterime role of early claming of uterine artery and delayed placental separation in reducing the consequences of placenta accreta spectrum disorders Patients and Methods Case series research was done in a Maternity Teaching Hospital as a single center study on twenty high-risk pregnant ladies at (32 to37 weeks) gestation diagnosed with placenta accrete through ultrasonography from the first of January 2021 to the first of November 2021. All patients were managed through the technique of delayed delivery of the placenta and early clamping uterine artery at the level of the internal os of the cervix using two vascular clamps followed by immediate ligation of the anterior branch of the internal iliac artery (IIA) in the retroperitoneal space within 1-2 minutes which shows a significant reduction in blood loss at placental bed following placental delivery, neither of cases ended by cesarean hysterectomy, written consent has been taken from the enrolled patients. A college has approved the study of the medicine Ethical Committee /the University of Sulaimani. Data from the current study has been analyzed using “IBM SPSS statistics version 25”. Results Among the patients who participated in the present study, the mean±SD of age was 37.1 ± 4.5 years range (30- 48) years old, and the mean±SD gestational age was 36 ± 1.5 range (32 to 38) weeks, their mean ±SD of BMI (body mass index) was 28 ± 2.2 (range, 24 to 32). The mean±SD cesarean count was 2.8 ± 1.3 (range, 0-5). The mean±SD of patients’ gravida and parity were 4.2 ± 1.6 (range,1-7) and 2.8 ± 1.4 (range,0-5), respectively. The mean±SD operation time varies 93 ± 25.6 range (60 to 120 minutes ); neither of the cases ended by hysterectomy, hemoglobin levels were also taken as part of the investigation, and its level preoperatively means ± SD 11.4 ± 1.1( range, 9.9 to 13.9) and post-operatively mean ± SD level was 9.6 ± 1.2 (range, 7.2 to 11.1), significantly less blood loss seen intraoperatively and only 75% of them require blood transfusion and only one-day hospital stay after the operation, no one requires the second laparotomy. Therefore, there was no significant association between them; thence, the mentioned procedure is clinically beneficial. Conclusion This method did not need to cesarean hysterectomy, so it causes less blood loss and morbidity.
Keywords: Placenta accrete; blood transfusion; cesarean hysterectomy